The rate of polymyalgia rheumatica (PMR) and remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome in a clinic where primary care physicians are working in Japan - Okumura, Toshikatsu (Springer-Verlag, 2011)
We analyzed the rate of polymyalgia rheumatica (PMR) and remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome, both characterized as seronegative inflammatory arthritis in elderly, in an outpatient unit where primary care physicians are working in Japan to better understand the epidemiological characteristics of the diseases in Japan. Consecutive outpatients who newly visited at Department of General Medicine, Asahikawa Medical University Hospital, Japan, between April 2004 and March 2010 were analyzed. Each parameter such as age, sex, diagnosis, and biochemical examination was investigated. During the 6 years, 10 or 3 patients were diagnosed as PMR or RS3PE syndrome, respectively. The patients with PMR were 7 women and 3 men, and the average age at diagnosis was 69. Out of all patients aged over 50 (n = 3,347), the rate of PMR was 0.22% in men or 0.36% in women, respectively. On the other hand, RS3PE syndrome was diagnosed in 3 men (76, 76, and 81 years old). The rate of patients with RS3PE syndrome was 0.09% among outpatients aged over 50 indicating that the rate of PMR in an outpatient clinic in Japan is not far from previous findings reported from western countries. When compared with PMR, the rate of RS3PE syndrome was approximately one-third, providing for the first time the rate of RS3PE syndrome when compared with PMR. These epidemilogical data might help us pick up the diseases in primary care setting in Japan.